Magnetic resonance enterography appraisal of lupus enteritis: A case report - Giuseppe Cicero, MD; Alfredo Blandino, MD; Tommaso D'Angelo, MD; Antonio Bottari, MD; Marco Cavallaro, MD; Giorgio Ascenti, MD; Silvio Mazziotti, MD (Radiology Case Reports, 2018)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with a multisystemic involvement. Usually, radiological imaging does not play a central role in evaluating SLE patients, although it may be helpful in assessing complications, allowing a more accurate evaluation of the patient. Lupus enteritis is one of the most common and potentially lethal manifestations of the gastrointestinal involvement of SLE. Among the imaging modalities, computed tomography scan is now considered the gold standard in evaluating lupus enteritis, although it is impaired by the radiation exposure. On the other hand, during the last decade magnetic resonance enterography has achieved a remarkable importance in evaluating small bowel lesions in patients affected by Crohn's disease. We describe the first case report of lupus enteritis evaluated with magnetic resonance enterography, putting forward the proposal of a reliable and radiation-free alternative to computed tomography scan in evaluating the intestinal involvement of SLE. Keywords: Magnetic resonance enterography, Lupus enteritis